Reduction in left atrial and pulmonary vein dimensions after ablation therapy is mediated by scar. (December 2021) - Gottlieb, Lisa A.; Al Jefairi, Nora; El Hamrani, Dounia; Naulin, Jérôme; Lamy, Jérôme; Kachenoura, Nadjia; Constantin, Marion; Quesson, Bruno; Cochet, Hubert; Coronel, Ruben; Dekker, Lukas R.C.
Graphical abstract: The reduction in LA and PV dimensions after ablation. Clinically successful PVI ablation decreased the PV and LA dimensions in AF patients (left panel). We make observations (right panel) that are compatible with the direct effect of ablation energy and subsequent scar formation causing the atrial downsizing. Abstract: Background: Ablative pulmonary vein isolation (PVI) decreases pulmonary vein (PV) and left atrial (LA) dimensions in atrial fibrillation (AF) patients. These changes are attributed to reverse structural remodeling following sinus rhythm restoration but evidence is lacking. We hypothesized that the downsizing is directly caused by the ablative energy and subsequent scar formation. Methods: We studied cardiac magnetic resonance imaging in 21 paroxysmal AF patients before and 3 months after successful PVI and in healthy sheep (n = 12) before and after PVI of the right PV only. Results: PVI decreased the PV diameter in patients and sheep by 11.0(10.3) and 9.2(11.0)%, (p < 0.001 and p = 0.020), respectively. The control left PV in sheep were unchanged. A linear correlation existed between the extent of PV scar and PVI-induced decrease in PV diameter in patients. After PVI, the LA volume decreased (103(38) vs. 92(31)ml, pre- vs. post-ablation, respectively, p = 0.006), while the right atrial (RA) volume was unchanged in patients. A decrease in active emptying fraction after ablation (26.5(10.7) vs. 21.8(10.6)%, pre- vs . post-ablation, p = 0.031) was associated with reduced contractility of the PV walls (p = 0.004). The contractility of the LA walls was unaltered (p = 0.749). Conclusion: The ablation-induced PV diameter reduction was similar in patients with AF and healthy sheep without AF and was associated with PV scar extent. The volume only decreased in LA and not RA after PVI, and wall contractility decreased only in ablated sites. Therefore, the PVI-induced atrial downsizing is caused by the ablative energy and subsequent scar formation.